An Analysis of Code-Switching in Speaking for Academic Purposes Class at PGRI Wiranegara University - Firdausi, Shima Putri; Mabaroh, Barotun; Istiqomah, Dewi Masitho (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
Speaking is the most important skill that must be mastered by students majoring in English education. Considering that English is a foreign language, the practice of code-switching can occur during the learning process by both lecturer and students. In this research, the researchers applied a descriptive qualitative method which aimed to know the types and functions of code-switching used by the lecturer and students in the Speaking for Academic Purposes Class. The result of this study showed that there are three types of code-switching that occurred in the class in accordance with Poplack’s theory, including tag-switching, intra-sentential switching, and inter-sentential switching. The researchers found 33 data of tag-switching, 102 data of intra-sentential switchig, and 32 data of inter-sentential switching. While, the code-switching functions included (1) filling in the blanks to sound fluent in speaking, (2) facilitating interaction, (3) conveying materials easier, (4) restating unknown words, and (5) reducing misunderstandings. The conclusion from this study is that code-switching often occurred in the Speaking for Academic Purposes class and the use of code-switching has several functions that make it easy for lecturer and students in the learning process.